Deliberative Democracy: A Malaysian Perspective (Journal of International Studies, 2020)
This paper discusses briefly first the theory of deliberative democracy as an important aspect of the democratic system of governance which encouragescitizens to participate in decision-making process by thinking and debating critically on issues that are political and of public interest especially with regard to policies that impact their daily lives and their future. This paper then analyses this theory from the Malaysian political perspective. Malaysia has different approaches toward implementing deliberative democracy. This is because of the nature of society and political circumstances of the country. While Malaysia rejects liberal democracy but it embraces elite deliberation which believes that democracy should be applied responsibly without jeopardising racial and religious harmony which calls for limiting certain democratic practices, such as freedom of speech and that of the press.